2022
DOI: 10.1109/jmw.2022.3152208
|View full text |Cite
|
Sign up to set email alerts
|

Sub-6 GHz High FOM Liquid Crystal Phase Shifter for Phased Array Antenna

Abstract: This paper presents a novel structure based on liquid crystal (LC) technology to achieve a high figure of merit (F OM) phase shifter that works at sub-6 GHz frequencies. The phase-shifting mechanism is enabled through the phase constant variation in the main microstrip line, which is loaded periodically by a variable equivalent capacitance controlled by a bias voltage. Furthermore, a systematic approach based on a transmission line circuit model and the periodic structure theory is developed as a fast method f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, since our design is also considered to be applied to a 2-dimensional array, the area of the circuit was very limited. Panahi et al [18] show a very attractive FoM of 105.9 • /dB at 4 GHz, but the space occupied by the phase shifter line is 616 mm 2 , much larger than the 70 mm 2 occupied by our proposed phase shifter. The loss is an essential factor in the phase shifter application, so we will continue to optimize the loss in future work.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…However, since our design is also considered to be applied to a 2-dimensional array, the area of the circuit was very limited. Panahi et al [18] show a very attractive FoM of 105.9 • /dB at 4 GHz, but the space occupied by the phase shifter line is 616 mm 2 , much larger than the 70 mm 2 occupied by our proposed phase shifter. The loss is an essential factor in the phase shifter application, so we will continue to optimize the loss in future work.…”
Section: Resultsmentioning
confidence: 56%
“…Recently, various research groups have reported the application of LCs to multiple circuits, such as frequencytunable planar antennas, phase shifters of microstrip and co-planar structures, frequency-tunable filters of waveguide structures, and beamforming array antennas [13], [14], [15], [16], [17], [18], [19], [20], [21], [22]. Several types of research have been conducted to reduce the response time of LC-based RF circuits.…”
Section: Introductionmentioning
confidence: 99%
“…This design combines the excitation source and radiation structure of the traditional holographic antenna to realize the integration of the antenna. Compared with the traditional phased array antenna, 9,10 the microwave holographic antenna does not need phase shifting units, making the structure more streamlined. Compared with the traditional reflective array antenna, 11,12 the feed form is more flexible, and the shielding of the feed can be avoided, greatly improving the monitoring range of the antenna system.…”
Section: Introductionmentioning
confidence: 99%